Automatic Circular Blade Sharpening Machine - Hari Shankar Elango, S.; Esakki Vigneswaran, E. (Asian Journal of Electrical Sciences, 2015)
The main purpose of this paper is to design and implement an Automatic circular blade sharpening machine using PIC16F877A and latest motor drivers .In this system we are having four outputs and two inputs. The four output devices are turntable motor, grinder motor, feed motor and a solenoid coil. And the two inputs are cycle start switch and home position sensor. This machine is designed to grind the blade in the shape of circular automatically which is designed for the beef flesh cutting application. The circular blade is to be mounted on the blade holder only by adjusting the center screw of the blade holder. Then we have to adjust the grinder motor position according to the diameter of the blade. By pressing the auto cycle start button after the completion of all the settings, the grinding cycle begins. After the grinding process the grinder motor will be settled down in its home position. And then the solenoid will be activated and it removes the burr with the help of turn table motor movement and thus the cycle will be completed.